Sequential Motion of 4D Printed Photopolymers with Broad Glass Transition. Issue 1 (12th December 2019) - Inverardi, Nicoletta; Pandini, Stefano; Bignotti, Fabio; Scalet, Giulia; Marconi, Stefania; Auricchio, Ferdinando
Abstract: The term "4D printing" refers to the development of stimulus‐responsive structures through 3D printing of active smart materials, typically shape memory polymers. A noteworthy aim of this research field is to obtain objects able to display complex shape‐shifting motions, such as sequential transformations over time. In this work, this peculiar response is studied on a commercial photopolymer, printed by stereolithography and featuring, on the basis of its inherent broad glass transition, the so‐called "temperature‐memory effect" (TME). The TME, that is, a response in which the shape memory effect occurs on a region controlled by the deformation temperature, is studied in shape memory cycles where the deformation temperature is systematically varied, so to provide a correlation between deformation and recovery temperatures. This also allows to properly select two temperatures at which deforming a specimen along a multistep history, so as to finally separate each recovery process on the temperature and time scales. This sequential recovery is studied in double folded bars, with arms deformed at different temperatures, and on a properly designed self‐locking clamp. The obtained results are promising for the realization of smart temperature‐responsive structures printed with one single polymer and capable of multiple shape transformations. Abstract : 4D printing is considered promising in various application fields due to the versatility and flexibility of the shape‐shifting feature in 3D printed stimuli‐responsive materials. Complex hierarchical shape‐shifting and sequential motions are here achieved in an original way by applying specific post‐processing thermo‐mechanical protocols to a 3D printed shape‐memory polymer characterized by a broad glass transition.